A macroeconomic model for forecasting crude oil prices with Feedforward Neural Network Grid Search Experimentation - Aunjum, Md. Ragib; Naqi, Muhammad; Jamil, Sifat (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.